GOVERNMENT POLICIES SHAPING HIGHER EDUCATION INSTITUTIONS: FOSTERING COLLABORATION BETWEEN UNIVERSITIES AND INDUSTRIES FOR TALENT DEVELOPMENT - Jehma, Hambalee (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The imperative for capacity building in bolstering a country’s economic growth and global competitiveness necessitates immediate advancements in both human resources and research and innovation acumen. This mandate aims to facilitate the recalibration of a nation's economic framework toward an innovation-driven economy. This systematic review, classified as a secondary study (Joanna Briggs Institute, 2013), conducted a methodical content analysis of qualitatively elicited data. Furthermore, it employed a comparative analysis (Barnett-Page et al., 2009) to scrutinize key components. The primary objective was to delve into the fundamental policies and strategies that attract talent, encompassing national initiatives, the roles of governing bodies, and related mechanisms. This exploration centered on case studies from Singapore, Malaysia, Taiwan, and China, grounded in the Triple Helix Model concept. This model underscores collaboration among public and private sectors alongside higher education institutions, presenting a pivotal mechanism for attracting and nurturing talent within a country's targeted industries, notably in technological advancements. The outcomes delineated that talent attraction strategies were intricately interwoven with national policies, entwined with research and innovation pursuits that directly correlated with a country's industrial and economic progression. Moreover, it highlighted the necessity of prioritizing human capital development to equip individuals with comprehensive knowledge, specialized skills, and expertise. These elements were identified as critical success factors, crucial for generating innovative solutions and advancing a nation's development agenda